Implementasi Konsep “Bound to Nature” pada Perancangan Interior Mangrove Edu-Tourism Centre di Surabaya - Laksono, David Ardi; Thamrin, Diana; Basuki, Lucky (Intra, 2018)
Problems that become the background of this design is because the people of Surabaya are less familiar with the existence of the mangrove ecosystem and the development of product’s potential by local SME’s in Surabaya. On the other hand, it is also due to inaccessibility and inadequate space to support these activities. The purpose of this design is to provide an alternative space to gather and introduce to the millennial generation to understand and experiment with the mangrove potential through educative, recreational, interactive, and local content approach, as well as the welfare of mangrove community. The design method used is the Disney method, which consists of 4 stages, which is spectator view, dreamers view, realists view, and critics view. The design result is a Mangrove Edu-Tourism Centre with the concept of Bound to Nature, with facilities include an open space lake, food stall, information and waiting area, SME product gallery, workshop studio, cultivation studio, staff room, lounge area, conservatory dome, sightseeing deck and teahouse. The author hopes that this design could provide solutions as well as being a global community space, with a micro efforts leads to a macro effects to help manage and save the mangrove environment in Surabaya.